Long-Term Survival Outcomes and Treatment Experience of 64 Patients With Esthesioneuroblastoma - Zeng, Qian; Tian, Yifu; He, Yihong; Xie, Qiongxuan; Ou, Ludi; Wang, Min; Chen, Wen; Wei, Rui (Frontiers in Oncology, 2021)
Background: Esthesioneuroblastoma (ENB) is a rare sinonasal malignancy, lacking a unified staging system and treatment. Management at a single center was retrospectively evaluated to inform future treatment options and prognostic factors. Methods: Clinical data of 64 consecutive ENB patients, including prognostic factors and treatment methods, were reviewed retrospectively. Data were collected to calculate overall survival (OS) and progression free survival (PFS). Results: The majority of tumors 84.4% were within Kadish C stage,79.7% were within T3 or T4, and 64.0% were within Hyams grade III or IV. A total of 50 (78.1%) patients received surgery and combined radiotherapy with or without chemotherapy, 10 (15.6%) received surgery with or without chemotherapy alone, and 4 (6.3 %) received radiotherapy with or without chemotherapy alone. The majority of patients (79.7%) underwent endoscopic resection (endoscopic and endoscopically assisted). Surgery combined with radiotherapy with or without chemotherapy resulted in significantly better OS (84.4% vs. 50.6%, 84.4% vs. 37.5%) compared to surgery alone and radiotherapy alone (P=0.0064). Endoscopic surgery group (endoscopic and endoscopically assisted) resulted in significantly better 5-year PFS (61.7% vs. 22.2%) compared to the open surgery group (P<0.001). Although endoscopic surgery group was not a statistically significant predictor of 5-year OS (P=0.54), the 5-year OS was 79.3% for the endoscopic surgery group and 76.2% for the open surgery group. A Cox regression analysis identified intracranial extension and surgery combined with radiotherapy as independent factors affecting 5-year OS while cervical lymph node metastasis and Hyams grade IV as independent factors affecting 5-year PFS. Conclusion: Our findings suggest that surgery combined with radiotherapy is the best treatment approach for ENB. For advanced tumors, endoscopic surgery is an effective treatment, and its survival rate is equal to or better than open surgery.